On the dielectric approximation in the additional light waves theory: an historical rehabilitation (recovery) - Piskovoi, V.N.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
After the basic Pekar papers on crystal optics with spatial dispersion (CSD) among a lot of others there was the “dielectric approximation” (DA) method. But soon it has been fully rejected because, as it was recognized by the main group of authors on the theme, it came in conflict with the law of conservation of energy flux through the ideal vacuum-crystal interface. The objective of this paper is to advance a way for rehabilitation of DA method by using indispensable broadening and essential generalization of the expression just for the energy flux density vector (EFDV) at the vacuum-medium interface (the so-called Poynting-Pekar vector in the additional light waves (ALW) theory).